Financial Risk Sharing with Providers in Health Maintenance Organizations, 1999 - Marsha R. Gold; Timothy Lake; Robert Hurley; Michael Sinclair (SAGE Publishing, 2002)
The transfer of financial risk from health maintenance organizations (HMOs) to providers is controversial. To provide timely national data on these practices, we conducted a telephone survey in 1999 of a multi-staged probability sample of HMOs in 20 of the nation's 60 largest markets, accounting for 86% of all HMO enrollees nationally. Among those sampled, 82% responded. We found that HMOs' provider networks with physicians, hospitals, skilled nursing homes, and home health agencies are complex and multi-tiered. Seventy-six percent of HMOs in our study use contracts for their HMO products that involve global, professional services, or hospital risk capitation to intermediate entities. These arrangements account for between 24.5 million and 27.4 million of the 55.9 million commercial and Medicare HMO enrollees in the 60 largest markets. While capitation arrangements are particularly common in California, they are more common elsewhere than many assume. The complex layering of risk sharing and delegation of care management responsibility raise questions about accountability and administrative costs in managed care. Do complex structures provide a way to involve providers more directly in managed care, or do they diffuse authority and add to administrative costs?